2015
DOI: 10.1007/s10549-014-3254-6
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk associated with benign breast disease: systematic review and meta-analysis

Abstract: Benign breast disease (BBD) is a broad category of diagnoses reported to convey a variable degree of increased risk of developing breast cancer. A meta-analysis of the existing literature was performed to quantify the risk estimate associated with BBD. Pubmed, Google Scholar, and EMBASE databases were searched in January 2011. English retrospective and prospective observational studies published from 1972 to 2010 evaluating BBD and the risk of breast cancer were included with data acquisition reported from 193… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
2
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(124 citation statements)
references
References 52 publications
4
99
2
19
Order By: Relevance
“…However, there was a very strong, statistically significant positive association between atypical hyperplasia and risk. The latter finding is in agreement with those of previous studies (1,2,13,42,43). Although only a small proportion of women with BBD are diagnosed with atypical hyperplasia, this lesion is potentially clinically relevant as it has been hypothesized that it may be a premalignant lesion, given that it contains some of the features that characterize breast cancers (44,45).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, there was a very strong, statistically significant positive association between atypical hyperplasia and risk. The latter finding is in agreement with those of previous studies (1,2,13,42,43). Although only a small proportion of women with BBD are diagnosed with atypical hyperplasia, this lesion is potentially clinically relevant as it has been hypothesized that it may be a premalignant lesion, given that it contains some of the features that characterize breast cancers (44,45).…”
Section: Discussionsupporting
confidence: 94%
“…Similar to previous studies, the current study showed an increased risk of breast cancer among women with epithelial hyperplasia without atypia although the association was not statistically significant (13,13,42,43). However, there was a very strong, statistically significant positive association between atypical hyperplasia and risk.…”
Section: Discussionsupporting
confidence: 87%
“…Some papers record that it is more frequent between the ages of 25 and 40 and others between 40 and 50, a phase which coincides with sexual maturity and consequently frequent hormonal disorders [1,8,22]. Table 1 shows that of a total of 401 patients, 61.0% were aged between 31 and 40 years and only 17.0% between 41 and 50.…”
Section: Discussionmentioning
confidence: 99%
“…Недавно был проведен метаанализ 32 эпидемиологических ре-троспективных и проспективных исследований о свя-зи мастопатии с риском рака МЖ. Средний возраст пациенток в период выявления мастопатии при биоп-сии составил 46,1 года, средний возраст диагноза рака МЖ -55,9, средний срок наблюдения -12,8 года (3,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)6); относительный риск рака МЖ при непро-лиферативных формах мастопатии статистически не-достоверно повышался до 1,17, при пролиферативных формах без атипии -статистически достоверно повы-шался до 1,76, при пролиферативных формах с ати-пией -до 3,93. Авторы делают вывод, что пролифера-тивные формы мастопатии как без атипии, так и с атипией значимо повышают риск рака МЖ [8].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified